2007
DOI: 10.1002/mop.22871
|View full text |Cite|
|
Sign up to set email alerts
|

Calibration of accelerometers by using an extrinsic fiber optic probe

Abstract: This article reports the principle of operation, design aspects, experimentation, and performance of an extrinsic fiber optic probe for the calibration of accelerometers. The device consists of fiber optic transmitter, fiber optic probe, minishaker type 4810, power amplifier type 2706, accelerometer, conditioning amplifier, dynamic signal analyzer, photodiode detector, and a digital multimeter. In this technique, the vibration amplitudes are measured simultaneously using an accelerometer and extrinsic fiber op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…At the same time the radiation pattern exhibited a lack of side lobes due to the spherical wave front generated by the antenna. Recently, it has been demonstrated that TEM horns with an elliptic flare profile are singularly well matched and exhibit almost frequency independent properties [10,11]. In this article, the principle of an elliptic flare is extended to an Xband waveguide horn in which both sides flare to form elliptic profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time the radiation pattern exhibited a lack of side lobes due to the spherical wave front generated by the antenna. Recently, it has been demonstrated that TEM horns with an elliptic flare profile are singularly well matched and exhibit almost frequency independent properties [10,11]. In this article, the principle of an elliptic flare is extended to an Xband waveguide horn in which both sides flare to form elliptic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…They are widely used as detectors of physical and chemical parameters, particularly in difficult measurement environments and as sensors of object positions and motions in the industrial setting. Reflective intensity-modulated fiber optic sensors using fiber optic probe have been extensively reported in literature [11][12][13]. Fiber optic probe may contain a bifurcated fiber bundle, a fiber bundle with transmitting and receiving fibers arranged in random, concentric, and semicircular configuration or large core polymer optical fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of OF into a wide variety of materials including composite materials offer immunity to harsh conditions, high sensitivity, multiplexing capability for sensing networks for different chemicals. These sensors have widely used to monitor environmental parameters such as position, vibration, strain, temperature, humidity, viscosity, chemicals, pressure, current, radiation, electric field and several other environmental factors [130][131][132]. In this section, we present a brief discussion on chemical sensor.…”
Section: Chemical Sensingmentioning
confidence: 99%
“…Fibre optic sensors have numerous applications in diverse branches of science and engineering, as is evident from a vast range of properties which has been sensed optically, ranging from light intensity, vibration, temperature, pressure, calibration of accelerometers, strain, liquid level, pH, chemical analysis, concentration, density, refractive index of liquids etc[ 19 20 ]. Refractometer are frequently used for the study of molecular structure and identification of organic compounds[ 21 22 ].…”
Section: Applicationsmentioning
confidence: 99%